Study on complex dynamics for the waste electrical and electronic equipment recycling activities oligarchs closed-loop supply chain - Zhu, Meihong; Li, Xiao; Ma, Junhai; Xu, Tiantong; Zhu, Liqing (Environmental science and pollution research international, 2022)
Nowadays, with more and more WEEE (waste electrical and electronic equipment) being abandoned, WEEE recycling activities are increasingly popular. In this paper, we build a closed-loop supply chain model and focus on the recycling behaviors of the members in this supply chain, which contains two manufacturers, the retailer, and the consumer. In the reverse chain, we set up dual channels and design two recycling methods: sell-back method and trade-in method. We use classical backward induction to run the model. And then we analyze the stability of the system and the impacts of some essential parameters by numerical simulation. The speed of the manufacture’s decision adjustment has a significant effect on the stability of the model. Manufacturers should adopt a stable rather than radical price adjustment strategy in order to achieve stable profit growth in the whole supply chain and avoid a chaotic price war. Manufacturers should increase innovation investment in recycling technology to reduce the cost of remanufacturing products and improve the initiative in market competition. In the end, we adopt the parameter control method and the decision-making method to control chaos, and they both have a good control effect.